Abelhas visitantes florais do algodoeiro (gossypium hirsutum) em quixeramobim e quixeré, estado do ceará, e seus efeitos na qualidade da fibra e semente - Silva, Eva Mônica Sarmento da (2007)
The present work aimed to study the bee species which visit flowers of cotton (Gossypium hirsutum), cultivar 187 8H, their respective pollination efficiencies in relation to crop pollination requirements, as well as their implications in cotton ball production, quality of fiber and seeds produced. Data were collected from May to August 2006 in commercial cropping areas in the counties of Quixeramobim and Quixeré, state of Ceará, Brazil. The area in Quixeramobim was small (10,000 m2), fertilized, close to native vegetation and used controlled insecticide applications, while the area in Quixeré was large (240,000 m2 ), non-fertilized, surrounded by other crop areas and submitted to systemic use of insecticide at every eight days. The research was split into four investigations: 1 – diversity and abundance of floral visitors to cotton flowers; 2 – foraging behavior of floral vistors to cotton flowers; 3 - floral biology, pollination requirements of cotton flowers, and pollination efficiency of Apis mellifera, and 4 – effect of Apis mellifera pollination in the physiological quality of cotton fiber and seeds. Floral visitors were observed, counted and captured by means of zig-zag walkings between the cropping lines. Experiments included bagging floral buds and hand pollination to evaluate cotton flowers’ pollination requirements and Apis mellifera pollination efficiency. Seed germination tests were carried out in the Seed Laboratory of the Universidade Federal do Ceará and fiber quality was evaluated in EMBRAPA Algodão, Campina Grande-PB. The experimental design was entirely randomized and the crossed factorial Place x Treatment (2x5). Data were analised using Anova F test submitted to variance analysis and compared a posteriori by the Tukey test or by means of General Linear Models, depending on the nature of data. The following insect species were collected visiting flowers in the experimental sites: Apis mellifera, Brachygastra lecheguana, Polybia ignobilis, Ancyloscelis sp. 1, Ancyloscelis sp. 2, Melissoptila uncicornis, Psaenythia sp. and Anthrenoides sp., the last three species being new occurrences in the state of Ceará. Floral visitors, resources gathered and foraging behavior were similar in both areas. Regarding floral biology, anthesis initiated early in the morning, from 6:00 h onwards, and all flowers were open by 7:00h. Stigmas were receptive from 6:00h to 13:00h, and pollen showed the greatest germinability (75%) after 10 hours of incubation. There were no significant differences (P>0.05) in fruit production among treatments in Quixeramobim and Quixeré. However, significant differences (P<0.05) were found among treatments within and/or between localities in variables such as cotton ball weight, seed weight, fiber weight, and number of seeds per fruit. In general, Quixeré showed lower means than Quixeramobim to all variables investigated. It was concluded that floral visitors’ frequency to cotton flowers was low in Quixeré and Quixeramobim, A. mellifera showed the greatest potential to act as biotic pollinator of cotton flowers due to its large numbers in the areas, but Melissoptila uncicornis Ancyloscelis sp. 1 and Ancyloscelis sp. 2 could become important native pollinators in conditions more favorable to their presence, such as reduced use of insecticides, smaller crop fields, less soil revolving, and more proximity to native vegetation. The cotton plant is a species with an intermediate pollination system, being able of autopollination, however it needs biotic agents and good nutritional conditions to maximize pollination. It was also possible to conclude that natural pollination levels occurring in the areas studied were not sufficient to maximize production and that plants in Quixeré were not in the best nutritional conditions, in opposition to what was observed in Quixeramobim. It was also concluded that A. mellifera bees could be relevant to cotton pollination since they increased the percentage of emergence and the index of plantule emergence velocity in cotton seeds. The intrinsic fiber characteristics were not affected by pollination.